Partial differential equations of hyperbolic type and applications - Geymonat, Giuseppe (World Scientific Pub. Co, 1987)
4 parts: Topics in spectral methods for hyperbolic equations; steady euler simulations using unstructured meshes; hyperbolic conservation laws and related topics;...; Quỹ Châu Á